Analisis Kelimpahan dan Identifikasi Predator Abalon (Haliotis squamata) di Pantai Geger, Nusa Dua, Bali - Jefry Cristian Bulan; I Gede Hendrawan; Ni Luh Putu Ria Puspitha (Journal of Marine Research and Technology, 2020)
This research was conducted at Geger Beach, Nusa Dua, Bali for 30 days. The purpose of this study was to determine the abundance of Haliotis squamata abalone predators at Geger Beach, Nusa Dua, Bali and to find out the types of Haliotis squamata abalone predators. The method used is Underwater Visual Census by using belt transects with a length of 50 meters with a distance of 2.5 meters left and right side 2.5 meters with a total area of 250 m2. This research was conducted at 3 different points with the addition of the abalone drum area as observations of more specific abalone predators with the help of cameras. The results of this study were the discovery of morey eel predators (Gymnothorax thyrsoideus) in the arae in the Haliotis squamata abalone drum and in the transect area there were more eels (Gymnothorax thyrsoideus) and Epinephelus sp. The results of predator abundance at point 1 were obtained for 0.0053 individuals / m2 for Gymnhotorax thyrsoideus type and for types of Epinephelus sp had a value of 0.0013 individual / m2, at point 2 it was 0.013 individuals / m2 for Gymnhotorax thyrsoideus and for Epinephelus sp has a value of 0.040 individuals / m2, at point 3 is 0.027 individuals / m2 for the type of Gymnhotorax thyrsoideus and for this type of Epinephelus sp has a value of 0.0013 individual / m2